Infiltrative mass of the skull base and nasopharynx: A diagnostic conundrum. Issue 2 (June 2015) - George, Manish M.; Goswamy, Jay; Solanki, Kohmal; Bhalla, Rajiv
Abstract: Inflammatory skull base masses are enigmatic and often behaviourally unpredictable. We present a case of idiopathic hypertrophic pachymeningitis (IHP) forming a central skull base mass to illustrate the process required when one investigates such skull base lesions. This is the first description of mass forming or tumefactive IHP extending into the nasopharynx. A 32-year old woman presented with frontal headaches and nasal discharge. She then deteriorated and was admitted with worsening headaches, serosanguinous nasal discharge and bilateral ophthalmoplegia. Multimodality imaging confirmed a destructive central skull base soft tissue mass involving the posterior clivus, floor of sphenoid sinus, nasopharynx and extending into both cavernous sinuses. Unfortunately, the patient continued to deteriorate despite treatment with broad-spectrum antibiotics. Cerebrospinal fluid, blood tests and transnasal biopsies for histology and microbiology did not reveal a diagnosis. Further neuroimaging revealed extension of the mass. Early corticosteroid treatment demonstrated radical improvement although an initial reducing regime resulted in significant rebound deterioration. She was stable on discharge with slowly reducing low dose oral prednisolone and azathioprine. We discuss the complexity of this case paying special attention to the process followed in order to arrive at a diagnosis of idiopathic hypertrophic pachymeningitis based on both the clinical progression and the detailed analysis of serial skull base imaging. Knowledge of the potential underlying aetiologies, characteristic radiological features, common pathogens and the impact on blood serology can narrow the potential differentials and may avoid the morbidity associated with extensive resective procedures. Highlights: Timely thorough investigation is critical to reduce the risk of irreversible damage. Prompt biopsy is essential to exclude both neoplasia and inflammatory conditions. Early corticosteroid administration is necessary to limit local infiltration.